Meta Analysis of Health Belief Model Theory on the Predictor of HPV Vaccine Uptake in Women of Reproductive Age - Nurul Qomariah; Bhisma Murti; Uki Retno Budihastuti (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Lack of knowledge about the use of HPV vaccine in women of productive age can result in cervical cancer. This study aims to determine the effect of the Health Belief Model application on the predictor of HPV vaccine uptake in women of reproductive age. Subjects and Method: Systematic review and meta-analyses were conducted using PRISMA guidelines and PICO model including: Population = women of reproductive age; Intervention= high perceived benefits, high perceived severity, high perceived susceptibility; Comparison= low perceived benefits, low perceived severity, low perceived susceptibility; Outcome= HPV vaccine uptake. Articles were collected from databases such as PubMed, Science Direct, and Google Scholar. The keywords used in the database search were